Dakwah kepada masyarakat bukan Islam menerusi interaksi - Akila, Mamat; Aminudin, Basir @ Ahmad (2012)
Ethnic diversity is one of the signs of the greatness of God in creating human aspects of Tawheed. Different colors, different physique and different languages are aspects of uniqueness and beauty of the creation of mankind. This uniqueness should be appreciated because it is one of Allah’s blessings upon mankind, and the best way to show our gratefulness for His blessings, is by having good interaction with different ethnic groups including non-Muslims. This article discusses Islamic da’wah to non-Muslims through interaction. It attempts to show that the teachings of Islam are positive in promoting interaction with non- Muslims even in terms of beliefs and values. This is important because to this day, some people in the west still have prejudices and stereotypes against Islam in the context of the interaction between Muslims and non-Muslims. To obtain knowledge and information for this article, the document analysis method has been used. This study found that Islam has laid the basis of fair interaction with non-Muslims. The findings also indicate that non-Muslims have the right to be respected. Moreover, the study also shows that Islamic da’wah triggers changes in the different communities of non-Muslims which are different from the arrival of Western colonist